2021
DOI: 10.3389/fpsyg.2021.666977
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Memory and Positivity Bias in the COVID-19 Health Crisis: The Effects of Aging

Abstract: This study aimed to determine whether the observed tendency to remember more positive than negative past events (positivity phenomena) also appears when recalling hypothetical events about the future. In this study, young, middle-aged, and older adults were presented with 28 statements about the future associated with the COVID-19 pandemic, half positive and half negative. In addition, half of these statements were endowed with personal implications while the other half had a more social connotations. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 94 publications
(146 reference statements)
1
14
0
1
Order By: Relevance
“…These results are consistent with the research by Gómez‐Corona et al ( 2021 ) who reported that the fear of consumers during the COVID‐19 pandemic are related to social, emotional, food supply, government, basic needs, food delivery, overeating, immunity, and family conflicts. The limitations of the present investigation lie mainly in the comparison of the words of emotions and memories against the results of other investigations where instruments from the health area or open text surveys are applied (Aizpurua et al, 2021 ; Johnson et al, 2020 ; Schelhorn et al, 2022 ; Zhao et al, 2021 ). However, these results give a guideline for the use of vocabularies of emotions and memories generated by the sensory field for their application within the health area in order to study cognitive changes in people with different diseases.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…These results are consistent with the research by Gómez‐Corona et al ( 2021 ) who reported that the fear of consumers during the COVID‐19 pandemic are related to social, emotional, food supply, government, basic needs, food delivery, overeating, immunity, and family conflicts. The limitations of the present investigation lie mainly in the comparison of the words of emotions and memories against the results of other investigations where instruments from the health area or open text surveys are applied (Aizpurua et al, 2021 ; Johnson et al, 2020 ; Schelhorn et al, 2022 ; Zhao et al, 2021 ). However, these results give a guideline for the use of vocabularies of emotions and memories generated by the sensory field for their application within the health area in order to study cognitive changes in people with different diseases.…”
Section: Resultsmentioning
confidence: 91%
“…This result can be attributed to the consumers recent COVID‐19 process, although the temporality (times higher than 30 days) of the elicited emotions and memories due to a COVID‐19 traumatic event is unknown. These results could also be an effect of regulation of the mood of people who suffered from the COVID‐19 disease (Aizpurua, Migueles, & Aranberri, 2021 ). According to Johnson, Saletti‐Cuesta, and Tumas ( 2020 ), positivity during the COVID‐19 pandemic may be a tendency to value social ties that are the cause of the demand for empathy and awareness to maintain health measures, especially the isolation that generates greater responsibility on the part of the population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding emotional regulation, the literature showed that older people's emotional experiences were more stable, positive, and a greater sense of well-being than younger people (Burr et al, 2021;Stone et al, 2010). According to Aizpurua et al (2021), older people have more pronounced adaptation mechanisms to adversity, stress, and emotionally negative events than younger ones. For instance, Carstensen et al (2020) found that older people had higher emotional well-being than younger people in the pandemic.…”
Section: Age and Well-beingmentioning
confidence: 99%